Revision of the western Nearctic species of Empis subgenus Enoplempis (Diptera: Empididae) - Sinclair, Bradley J.; Brooks, Scott E.; Cumming, Jeffrey M. (Zootaxa, 2025)
The species of the Empis subgenus Enoplempis Bigot from western North America, including the Rocky Mountains westward, are revised. A total of 75 species are recorded from this region, including 54 new species. The western species are classified into 12 species groups as follows: the Empis (En.) arrecta species group—E. (En.) arrecta sp. nov., E. (En.) diokra sp. nov., E. (En.) occidentalis sp. nov., E. (En.) shoshona sp. nov.; the Empis (En.) bigoti species group—E. (En.) aerobatica Melander, E. (En.) bigoti Melander, E. (En.) collinsi sp. nov., E. (En.) montgomeryi sp. nov., E. (En.) multifaria sp. nov., E. (En.) paraerobatica sp. nov., E. (En.) podagra Melander; the Empis (En.) canaster species group—E. (En.) arizonensis sp. nov., E. (En.) canaster Melander, E. (En.) chillcotti sp. nov., E. (En.) contrasta sp. nov., E. (En.) falcata Melander, E. (En.) fitzgeraldi sp. nov., E. (En.) safra sp. nov., E. (En.) sagehenensis sp. nov., E. (En.) spokanensis sp. nov., E. (En.) subcanaster sp. nov.; the Empis (En.) clava species group—E. (En.) clava sp. nov., E. (En.) mariposa sp. nov., E. (En.) tularensis sp. nov.; the Empis (En.) delumbis species group—E. (En.) delumbis Melander, E. (En.) floricola sp. nov., E. (En.) sphaera sp. nov., E. (En.) spiculata sp. nov., E. (En.) tripenicillata sp. nov.; the Empis (En.) geneatis species group—E. (En.) fisheri sp. nov., E. (En.) geneatis (Melander), E. (En.) oharai sp. nov., E. (En.) subgeneatis sp. nov.; the Empis (En.) manca species group—E. (En.) bova sp. nov., E. (En.) manca Coquillett, E. (En.) submanca sp. nov., E. (En.) wilderae sp. nov.; the Empis (En.) mira species group—E. (En.) macdonaldi Sinclair, Brooks & Cumming, E. (En.) mira (Bigot), E. (En.) submira Sinclair, Brooks & Cumming, E. (En.) williamturneri Sinclair, Brooks & Cumming, E. (En.) winkleri Sinclair, Brooks & Cumming; the Empis (En.) nodipoplitea species group—E. (En.) nodipoplitea Steyskal; the Empis (En.) teres species group—E. (En.) scotti sp. nov., E. (En.) scutica sp. nov., E. (En.) teres Melander, E. (En.) undulasetosa sp. nov.; the Empis (En.) turgida species group—E. (En.) turgida sp. nov., E. (En.) woodleyi sp. nov.; and the Empis (En.) valentis species group—E. (En.) aeripes Melander, E. (En.) disconvenita Melander, E. (En.) dolabraria Melander stat. rev., E. (En.) flavobulla sp. nov., E. (En.) fresno sp. nov., E. (En.) mixopolia Melander, E. (En.) paraeripes sp. nov., E. (En.) subaeripes sp. nov., E. (En.) valentis Coquillett. Additionally, the following 17 western species are unplaced to species group: E. (En.) aphela sp. nov., E. (En.) blodgettensis sp. nov., E. (En.) californica sp. nov., E. (En.) cerina sp. nov., E. (En.) culcitella sp. nov., E. (En.) delnortensis sp. nov., E. (En.) dubitata sp. nov., E. (En.) genista sp. nov., E. (En.) holoptica sp. nov., E. (En.) manning sp. nov., E. (En.) missoula sp. nov., E. (En.) oregonensis sp. nov., E. (En.) poplitea Loew, E. (En.) richardvockerothi sp. nov., E. (En.) sierraensis sp. nov., E. (En.) susanae sp. nov., E. (En.) yakimensis sp. nov. The following new synonymy is designated: E. (En.) bullifera Kessel & Kessel = E. (En.) bigoti. Lectotypes are designated for the following species: E. (En.) aeripes, E. (En.) disconvenita, E. (En.) dolabraria, E. (En.) mixopolia, E. (En.) aerobatica, E. (En.) podagra, E. (En.) canaster, E. (En.) falcata, E. (En.) delumbis, E. (En.) manca, E. (En.) teres and E. (En.) poplitea. A key to all the western species is presented with distributions illustrated. The form of nuptial gift presentation displayed within this group, including the use of balloons (with or without prey) and unwrapped prey is indicated for species when known. In addition, new eastern records are listed and two new species from eastern North America are described (E. (En.) deceptiva sp. nov. and E. (En.) joanae sp. nov.). A complete list of all known species and species groups in the subgenus Enoplempis is also provided.